Acute bilateral paramedian thalamic infarct in the differential diagnosis of hyperactive delirium: A case report - Eren, Fettah; Demir, Aysegul (Journal of Surgery and Medicine, 2021)
Acute bilateral paramedian thalamic infarct is a rare condition. Changes in consciousness, hypersomnia, mood disorders, cognitive problems and paralysis of vertical gaze may be observed in patients with acute bilateral paramedian thalamic infarct. Although it may have many causes, the most common is atherosclerotic small vessel disease. Some patients, who present with isolated neuro-psychiatric symptoms, may be misdiagnosed with a psychiatric illness. We herein present a patient presenting with the clinical features of hyperactive delirium who was diagnosed with acute bilateral paramedian ischemia. A 53-year-old female patient was admitted with complaints of changes in consciousness, agitation, and impairments in attention and memory, starting 2 days earlier and fluctuating during the day. Her history revealed hypertension and obesity. Levels of serum total cholesterol, high density lipoprotein (LDL) cholesterol and triglyceride were high, and the cardiac evaluation was within normal limits. Acute paramedian thalamic ischemia was detected through neuroimaging. Thalamic infarcts display different clinical features according to the localization of the lesions. Although many neurological and neuropsychological symptoms may be seen, thalamic infarcts may also present with psychiatric symptoms alone. Therefore, thalamic lesions should also be considered in acute or subacute behavioral changes in patients with no history of psychiatric disorders.